Determination of Bismuth in Bottled and Mineral Water Samples at Trace Levels by T-Shaped Slotted Quartz tube-Atom Trap-Flame Atomic Absorption Spectrometry - Bodur, Suleyman; Erarpat, Sezin; Chormey, Dotse Selali; Buyukpinar, Cagdas; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2019)
An accurate and reliable analytical method for the determination of bismuth at trace levels in bottled and mineral water samples has been developed based on hydrogen assisted T-shape slotted quartz tube-atom trap-flame atomic absorption spectrometry (T-SQT-AT-FAAS). Conventional FAAS is not sufficiently sensitive to measure trace and ultra-trace levels of metals due to the low nebulization efficiency and short residence time of atoms in the light path. To overcome this problem, atom trapping with a T-shaped slotted quartz tube was coupled to the FAAS system. Bismuth atoms were trapped on the surface of T-SQT and released by hydrogen gas, which provided a reducing environment. All of the system parameters such as flame type, hydrogen flow rate, the height of T-SQT from the burner head, and trapping period were optimized to enhance the analytical signal to attain low detection limits. After obtaining the optimum conditions, the limit of detection and limit of quantitation of the developed method were found to be 0.95 and 3.2 mu g L-1, respectively. Recovery values were obtained between 90% and 104% that showed good accuracy and applicability of the proposed method to the analysis of bottled and mineral water samples.
Keywords: Atom trapping; bismuth slotted quartz tube; T-shape slotted quartz tube-atom trap-flame atomic absorption spectrometry (T-SQT-AT-FAAS); LIQUID-LIQUID MICROEXTRACTION; SENSITIVE DETERMINATION; PRECONCENTRATION; LEAD; CADMIUM; COPPER; AAS; Chemistry